Unpublished Qitaat of Ameer Meenai - Dr. Sadaf Tabassum (Zaban-o-Adab, 2023)
The name of Amir Ahmad Amir Minai needs no introduction in Urdu poetry. He was born in Lucknow in 1829 according to 1244 AH and died in 1900 according to 1318 AH. He wrote Naat, qasida, masnawi, wasukht, riddles, sayings, salam, suhare, tarkeeb-band, tarjee-band, qitat, rubai and chronology, etc. are all included. There are also many rubaiat and historical sections in Amir's published speech. These types of stanzas (quatrains) are somewhat different from each other in terms of structure. In literary terms, a quatrain (Qita) is a poem that appears to be a cut part of a ghazal or qasida are connected and continuous. In this paper, those unpublished pieces(Qitat) of Amir Meenai are included which do not fall into the category of history but have a unique position in terms of the diversity of their topics, literature, ethics and knowledge in their pieces.